Fine-scale habitat suitability and connectivity analysis for the core populations of Yellow-spotted mountain pond-breeding newt (Neurergus derjugini) in the west of Iran and east of Iraq - Peyman Karami; Sajad Tavakoli; Mina Esmaeili (Global Ecology and Conservation, 2023)
Amphibians are among the largest endangered groups globally, with more than 2000 endangered species. As low mobility limits species' distribution, connectivity between core populations is essential. The evolutionary characteristics of amphibians, especially those more water-dependent, have faced the study of habitat connectivity with the challenge of Movement Context (MC), for which water and moisture are integral parts. This fine-scale study was performed to assess the distribution of Neurergus derjugini in western Iran and eastern Iraq and identify potential linkages between the core populations using the physical structures that play an MC role in the landscape. Distribution modeling was executed using maximum entropy modeling (MaxEnt). Core populations were organized based on the home range size of N. derjugini, and the inverse of the habitat suitability was used as a resistance surface. The connectivity of core populations was modeled by integrating Electronic Circuit Theory and Least Cost Paths (LCPs) in the Linkage Mapper toolbox. The MC was characterized in the drainage basins based on the slope position and landform categories. Three scenarios were developed for connecting the core populations. In Scenario 1, drainage basins, in Scenario 2, valleys and in Scenario 3, canyons, shallow valleys, headwaters, and U-shaped valleys were considered to be MCs. Among the variables, slope and DEM diversity (H) had the greatest influence on the distribution of N. derjugini. There were 12 basins in the study area, while core populations were scattered only in three basins.Most of the presence points (63.38 %) and the highest quality linkages between the core populations were located in only one basin. Depending on movement ability and the physiological limits of the newts, the proxy did not work effectively in Scenario 1, and linkages were exaggerated. Compared to Scenario 2, linkages in Scenario 3 were more compatible with the ecological and biological characteristics of the species. Based on the results, fine-scale modeling could lead to reliable results for the MC-dependent species. Continuity in the structure of the physical landscape is crucial to the connectivity of core populations. Salamanders are irregularly distributed and dispersed.Thus, proper distribution of adjacent core populations in valleys and streams could be regarded as a successful step in the establishment of population connectivity. With the arrival of seasonal rainfall and snowmelt, temporary ponds are formed, which serve as stepping stones that increase the likelihood of distribution.